Can transparent disclosure be the solution to resolve shari’ah and ethical issues in special reserves of Islamic banks in Malaysia? - Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Journals of Multidisciplinary Research Academy (IJMRA), 2013)
Islamic banks cannot promise to pay fixed rate of return to the depositors although they are trying to pay at least the same rate of return provided by the conventional banks. Changes in interest rate put additional pressure on the Islamic banks to compete with the conventional banks. One way to compete the rate provided by the conventional banks is to reserve some portion of profit to cover in the case of incurring losses from the investment. In Malaysia, Islamic banks are allowed to keep profit equalization reserve and investment rate reserve. However, there is no research has been done to examine any Shari’ah issues regarding these reserves. Therefore, this research focuses on these issues. The findings show that these issues are arisen due to using conventional rate of return as benchmark and deviation of the practice of these reserves from the original concepts of profit and loss sharing concept applied in the Islamic banks, negative impacts on zakat and income tax and no harmonization and standardization on the practices. It is believed that these issues can be solved and valid from the ethical and Shari’ah aspects investment account holders are well informed about these reserves and they agree on these practices. We expect that these issues should be revisited by the Shari’ah scholars, industrial players and regulators to ensure that all the involved parties are treated fairly.